Normativa internacional de protección de la infancia - Ocón Domingo, José (Cuadernos de Trabajo Social, 2006)
Even if it is true that, depending on the different models of childhood typical of each historic period, the rights and interests of minors have been barely guaranteed, an important change of direction occurs in the 20 century. The disasters caused by the two World Wars have an important effect on the domestic legislation in force in different countries. Spain, too, despite the delays caused by Franco’s dictatorship, now has a modern child protection system.Indeed, with the implementation of the democratic system, our legislation reflects the philosophy that guides international rules, essentially inspired by the Convention on the Rights of the Child (1989). In this paper, in addition to this Convention, we analyze other legislation that has contributed to the updating of the legal system charged with the defense and promotion of the rights of children.